The Function of Self-Harm Behavior in a Forensic Population - Jeglic, Elizabeth L. (International journal of offender therapy and comparative criminology, 2005)
This article examines the functions of self-injurious behavior (SIB) in forensic populations. The cases of four individual offenders who have engaged in SIB are presented. These cases depict the four main functions of self-harm behaviors including (a) suicidal intent, (b) manipulation of the environment, (c) emotion regulation, and (d) a response to psychotic delusions or hallucinations. Assessment and treatment implications are discussed